First Observation of the Nocturnal Cleaning Relationship between Common Octopus Octopus vulgaris (Cuvier, 1797), and Indo-Pacific Palaemonid Shrimp, Urocaridella pulchella YokeÅŸ & Galil, 2006 from the Iskenderun Bay, Eastern Mediterranean Coast of Turkey - Ergüden, Deniz; Ayas, Deniz; Uyğur, Necdet (Acta Aquatica: Aquatic Sciences Journal, 2021)
During a Scuba survey in Iskenderun Bay at night time on November 2018, a female Urocaridella pulchella individual was observed with nocturnal cleaning on Octopus vulgaris at 16 m in depth. Some photos of the shrimp and its symbiont were taken. Although the nocturnal cleaning relationship between U. pulchella and various marine species has been reported in some studies, the nocturnal cleaning relationship between O. vulgaris and U. pulchella has been observed for the first time. In addition, in the present study, we first reported Indo-Pacific palaemonid shrimp U. pulchella which was encountered in its natural habitat during an underwater observation from Iskenderun Bay, and this report is the first observation for this area and fills a gap in the distribution range of this species.Keywords: eastern Mediterranean, Iskenderun coast, nocturnal cleaning, Palaemonidae, Turkey.